Comparative Proteomic Analysis of Susceptible and Resistant Rice Plants during Early Infestation by Small Brown Planthopper - Dong, Yan; Fang, Xianping; Yang, Yong; Xue, Gang-Ping; Chen, Xian; Zhang, Weilin; Wang, Xuming; Yu, Chulang; Zhou, Jie; Mei, Qiong; Fang, Wang; Yan, Chengqi; et al. (Frontiers in Plant Science, 2017)
The small brown planthopper (Laodelphax striatellus Fallén, Homoptera, Delphacidae-SBPH) is one of the major destructive pests of rice (Oryza sativa L.). Understanding on how rice responds to SBPH infestation will contribute to developing strategies for SBPH control. However, the response of rice plant to SBPH is poorly understood. In this study, two contrasting rice genotypes, Pf9279-4 (SBPH-resistant) and 02428 (SBPH-susceptible), were used for comparative analysis of protein profiles in the leaf sheath of rice plants in responses to SBPH infestation. One hundred and thirty-two protein spots that were differentially expressed between the resistant and susceptible rice lines were identified with significant intensity differences (≥2-fold, P < 0.05) at 0, 6, and 12 h after SBPH infestation. Protein expression profile analysis in the leaf sheath of SBPH-resistant and SBPH-susceptible rice lines after SBPH infestation showed that proteins induced by SBPH feeding were involved mainly in stress response, photosynthesis, protein metabolic process, carbohydrate metabolic process, energy metabolism, cell wall-related proteins, amino acid metabolism and transcriptional regulation. Gene expression analysis of 24 differentially expressed proteins (DEPs) showed that more than 50% DEPs were positively correlated with their mRNA levels. Analysis of some physiological indexes mainly involved in the removal of oxygen reactive species showed that the levels of superoxide dismutase (SOD) and glutathione (GSH) were considerably higher in Pf9279-4 than 02428 during SBPH infestation. The catalase (CAT) activity and hydroxyl radical inhibition were lower in Pf9279-4 than 02428. Analysis of enzyme activities indicates that Pf9279-4 rice plants defend against SBPH through the activation of the pathway of the salicylic acid (SA)-dependent systemic acquired resistance. In conclusion, this study provides some insights into the molecular networks involved on cellular and physiological responses to SBPH infestation.